2016
DOI: 10.18203/2320-6012.ijrms20164554
|View full text |Cite
|
Sign up to set email alerts
|

Association of non-alcoholic fatty liver disease with anthropometric and metabolic parameters in type 2 diabetes: a retrospective analysis

Abstract: Background: Type 2 diabetes (T2D) is associated with increased prevalence of non-alcoholic fatty liver disease (NAFLD) which mediates increased insulin resistance and is associated with cardiovascular disease (CVD) risk factors. Aim of the study was to understand the association of NAFLD with anthropometric and metabolic parameters in T2DM.Methods: A retrospective observation of data obtained from a private diabetes care centre in non-alcoholic T2D patients was performed. Association of presence of NAFLD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In the present study, the AUC of the ROC analyses showed that the area under the curve to predict pre-diabetes using WHR was higher in females compared to males (0.750 and 0.693, respectively) [ 17 ]. Few studies in India had also shown a similar correlation between MAFLD and diabetes as well as prediabetes [ 18 - 21 ]. A concurrent study which was conducted by the University of Oradea in Romania showed 93.20±7.24 with a P-value of 0.02.7.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the AUC of the ROC analyses showed that the area under the curve to predict pre-diabetes using WHR was higher in females compared to males (0.750 and 0.693, respectively) [ 17 ]. Few studies in India had also shown a similar correlation between MAFLD and diabetes as well as prediabetes [ 18 - 21 ]. A concurrent study which was conducted by the University of Oradea in Romania showed 93.20±7.24 with a P-value of 0.02.7.…”
Section: Discussionmentioning
confidence: 92%